Rhetoric of Public Policy: Ethos, Logos and Pathos in Development Governance (Rural Development Journal, 2026)
The study explores the definition of public policy as a technocratic function and examines the underlying capacity of rhetoric to persuade the public in the developmental setting. It is common to describe public policy as a technical, logical process of making decisions based on facts. However, academic research indicates that policy is essentially a rhetorical and communicative activity in which narratives and persuasion are crucial to gaining legitimacy. Using the Aristotelian triad of ethos (credibility), logos (logic), and pathos (emotion) as an analytical framework, this study explores the crucial role of rhetoric in public policy and development. With an emphasis on Nepal's changing policy environment, the study uses a qualitative, interpretive design to analyze national development plans, policy documents, and international agreements. The results show that Nepal's development discourse is marked by pathos, using aspirational narratives of national pride and inclusion to navigate political transitions and post-conflict reconstruction, whereas international development organizations heavily rely on logos-dominated technocratic language to project neutrality. The study also looks at how these rhetorical techniques are used to create institutional trust and public consent in times of crisis, like the COVID-19 pandemic and the 2015 earthquake. The study comes to the conclusion that rhetoric is a fundamental component of governance rather than an incidental aspect. In order to close the gap between policy intentions and lived realities in sustainable development, it makes the case for a move toward ethical rhetoric a practice that strikes a balance between